Jewellery box: inspired by Royale Theater Shah Alam / Muhammad Hasri Abdul Azis - Abdul Azis, Muhammad Hasri (2022)
Shah Alam Royal Theatre is one of Malaysia landmark that very unique in its shape and architectural that very unique in its shape and architectural structure compared to other building, it has tons of structure compared to other building, it has tons of edges but has very well define curve. This complexity edges but has very well define curve. This complexity brings out the modern look in traditional way brings out the modern look in traditional way. Jewellery Box is a box that was made to preserve the jewellery when not in used. This box was heavily inspired by this magnificent Malaysia building that is very rare in it geometry structure, making it look unique and outstanding.